2022
DOI: 10.3389/fmars.2022.885614
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Photocatalytic Removal of Microplastics: Mechanisms, Kinetic Degradation, and Reactor Design

Abstract: Plastic products are used in almost all aspects of our daily life. Due to their low cost, portability, durability, and resistance to degradation, these products are affecting the health of the environment and biota on a global scale. Thus, the removal and mineralization of microplastics is an important challenge in the 21st century. Advanced oxidation processes (AOPs) have recently been identified as a viable treatment technique for tackling recalcitrant organic molecules and polymers. However, information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 255 publications
0
21
0
Order By: Relevance
“…AOP‐assisted MP degradation from the aqueous matrices was evaluated by Rizwan and Bilal (2022). Hamd et al (2022) explain the mechanisms, kinetic degradation and recent advances in reactor design for the photocatalytic removal of MPs. Innovative catalytic processes, such as PC, enhanced oxidation and biotechnology, offer eco‐friendly alternatives to the current MP waste disposal and produce usable products from MPs and plastic trash (Chen et al, 2022a).…”
Section: Aopsmentioning
confidence: 99%
See 1 more Smart Citation
“…AOP‐assisted MP degradation from the aqueous matrices was evaluated by Rizwan and Bilal (2022). Hamd et al (2022) explain the mechanisms, kinetic degradation and recent advances in reactor design for the photocatalytic removal of MPs. Innovative catalytic processes, such as PC, enhanced oxidation and biotechnology, offer eco‐friendly alternatives to the current MP waste disposal and produce usable products from MPs and plastic trash (Chen et al, 2022a).…”
Section: Aopsmentioning
confidence: 99%
“…They pointed out the difficulties and challenges related to the separation, deterioration and subsequent recycling of micro/nanoplastics in urban waterways. AOP-assisted MP degradation from the aqueous matrices was evaluated byRizwan and Bilal (2022) Hamd et al (2022). explain the mechanisms, kinetic degradation and recent advances in reactor design for the photocatalytic removal of MPs.…”
mentioning
confidence: 99%
“…These MPs may eventually result in the aquatic ecosystem. Studies on WTP from various sites revealed that an excessive quantity of MPs in the treated water ranges between 5.00 × 10 5 and 1.39 × 10 10 particles (Hamd et al, 2022). As per the scientific reports, there is still no distinct approach in any WTP for the elimination of MPs.…”
Section: Limitations Of Current Techniquesmentioning
confidence: 99%
“…The TiO 2 -embedment approach was used to degrade plastics such as PE, PP, PVC, PS, and PS polymers under diverse parameters (Fa et al, 2013;Nabi et al, 2020;Hamd et al, 2022). The PCD of PS plastics was carried out under UV irradiation using PS-TiO 2 composite.…”
Section: Titanium Dioxide Assisted Photocatalytic Degradation Of Micr...mentioning
confidence: 99%
“…However, recycling microplastic contaminant particles from the ocean and applying them to solar collectors not only helps to improve marine ecology but also improves the heat transfer performance of solar collectors. In addition, research on the radiative properties of microplastic particles can also be employed to enhance microalgal photosynthesis in a medium polluted with microplastics ( Hamd et al, 2022 ). Research has shown that the addition of nano- and micron-particle suspensions to the conventional solar collector can improve its heat transfer performance ( Devendiran and Amirtham, 2016 ; Turkyilmazoglu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%